The Nonlinear Impact of Economic Growth Pressure on Urban Land Green Utilization Efficiency—Empirical Research from China - Xinyue Wang; Kegao Yan; Yang Shi; Han Hu; Shanjun Mao (Land, 2025)
China’s unique economic growth target system exerts significant economic growth pressure (EGP) on local officials, leading to notable economic and environmental consequences for urban land use. Consequently, this system is theoretically expected to have a significant impact on urban land green utilization efficiency (ULGUE). This study investigates the invisible institutional factors that shape ULGUE within China’s distinct economic growth target system. The results indicate an inverted U-shaped relationship between EGP and ULGUE, and this nonlinear relationship is statistically significant in central, western, and northeastern cities but not in eastern cities. EGP influences ULGUE in a non-monotonic manner by affecting land marketization, green technology innovation, and industrial structure upgrading. Furthermore, environmental regulation and financial technology investment moderate the relationship between EGP and ULGUE. Heterogeneity analysis reveals that the inverted U-shaped relationship is more pronounced in resource-dependent cities and cities with stringent target constraints. This study contributes empirical evidence on the interaction between EGP and ULGUE while offering both theoretical insights and practical implications.